Psychiatry : Made Easy - Anbu, T. (New Delhi : Jaypee Brothers, 2014)
Concise guide to the field of psychiatry for trainees, covering numerous different disorders. Includes a comprehensive appendices section listing and defining common defence mechanisms, phobias, manias and paraphilias, and a detailed glossary
Keywords: Psychiatry -- Made Easy